Enhancing Islamic Educational Outcomes through Community-Based Research: a Ramadan Intervention Program at Pondok Tahfidz Az-Zikri - Bahrul Ulum; Satri Yarnis; Jihan Chairatunnisa; Luthfia Rahma; Fitria Nur Ikhsani; Siti Aminah Nasution; Vira Milta Rusdy (ASSUNNAH PRESS, 2025)
This study examines the implementation and outcomes of a Community-Based Research (CBR) intervention conducted at Pondok Tahfidz Az-Zikri Lubuak Batingkok, an Islamic educational institution specializing in Quranic memorization. The research addresses the institution's identified limitations in teaching comprehensive Islamic practices beyond Quranic memorization. Female students from STAI Assunnah implemented a structured 20-day program during Ramadan 2024 through a Field Work Course (KKL), employing action research methodology comprising planning, implementation, reflection, and evaluation phases. The intervention utilized lecture and talaqqi methods to deliver a curriculum focused on worship practices, Quranic recitation improvement, hadith memorization, and supplication instruction. Data collection employed interviews, observation, and questionnaires with qualitative descriptive analysis. Results demonstrate a 30% improvement in jurisprudential understanding and 75% enhancement in supplication and hadith memorization among participants. The program successfully integrated theoretical knowledge with practical application through experiential learning activities including communal work, nature contemplation, and monitored congregational prayers. This research contributes to the literature on community-based educational interventions in Islamic institutions by demonstrating the efficacy of structured religious education programs during intensive worship periods. The study recommends longitudinal assessment of sustained impact, curriculum integration beyond Ramadan, and comparative analyses across diverse institutional settings to enhance generalizability and refine pedagogical approaches for Islamic education in non-formal environments